ANALISIS KONDISI SOSIAL-EKONOMI MASYARAKAT MIGRAN SEBELUM DAN SESUDAH BERADA DI KOTA TIMIKA - Muhamad Nur Lausiry; Leonardus Tumuka (Delilah Tinggi Ilmu Ekonomi Jambatan Bulan, 2019)
The purpose of this study was to determine differences in the socio-economic conditions of migrant communities before and after being in the city of Timika. This study used a comparative and descriptive research method, where a comparative method was used to compare the socio-economic conditions of migrant communities before and after being in the city of Timika, while the descriptive method was used to describe the socio-economic conditions of migrant communities in the area of ​​origin and after being in Timika. The type of data in this study is quantitative obtained from a sample of 300 respondents from migrant communities in the city of Timika. The sampling technique in this study uses a random sampling technique, which is part of probability sampling. The variable socio-economic conditions of migrants measured in this study are employment and income level, both in the area of ​​origin, and after being in the city of Timika. The data analysis used in this study is the analysis of the sign test. The results of this study indicate that there are differences in the economic conditions of migrant communities in the area of ​​origin after being in the city of Timika.